RETRACTED: Organizational and economic aspects of managing financial policy, sustainable growth and development of the corporation - Tatarintseva Svetlana; Liberova Alexandra (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001